2021
DOI: 10.2196/26875
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Unobtrusive Monitoring to Support Home-Based Dementia Care: Qualitative Study Among Formal and Informal Caregivers

Abstract: Background Due to a growing shortage in residential care, people with dementia will increasingly be encouraged to live at home for longer. Although people with dementia prefer extended independent living, this also puts more pressure on both their informal and formal care networks. To support (in)formal caregivers of people with dementia, there is growing interest in unobtrusive contactless in-home monitoring technologies that allow caregivers to remotely monitor the lifestyle, health, and safety o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…We found that privacy and ethical issues were frequently mentioned as a barrier in relation to this type of technology; however, ways to overcome this barrier have mostly been unaddressed. In a previous study among potential users, we found that artificial intelligence–driven monitoring systems particularly require introduction in a way that prevents caregivers from feeling undervalued [ 50 ]. We have published a set of requirements that can benefit the development and introduction of in-home monitoring technologies aimed at supporting home-based dementia care [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that privacy and ethical issues were frequently mentioned as a barrier in relation to this type of technology; however, ways to overcome this barrier have mostly been unaddressed. In a previous study among potential users, we found that artificial intelligence–driven monitoring systems particularly require introduction in a way that prevents caregivers from feeling undervalued [ 50 ]. We have published a set of requirements that can benefit the development and introduction of in-home monitoring technologies aimed at supporting home-based dementia care [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For older adult care, it is important to monitor activities that are relevant to various stakeholders. For example, a system that can unobtrusively detect what a person is typing on a keyboard is of no use for older adult care, whereas systems that can unobtrusively monitor falls, personal hygiene, and sleep patterns are more useful for older adult care [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…The system will be more acceptable if it measures the behaviors that are in line with the needs of stakeholders and are part of the daily routine of the older adults. From the results of a qualitative study among formal or informal caregivers of persons with dementia, it can be concluded that sensing technology should be used to monitor the risk of falls, personal hygiene, nocturnal restlessness, and eating and drinking patterns [ 9 ]. In accordance with the routine dimension of the conceptual framework, if the system is unobtrusive, it will not impact the daily routine while using such monitoring devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations